Validation of a biomechanical performance assessment platform applying an inertial-bpased biosensor and axis vector computation - Kim, W.; Kohles, S.; Vela, E.; Huayamave, V. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
Inertial kinetics and kinematics have substantial influences on human biomechanical function. A new algorithm for IMU-based motion tracking is presented in this work. This study combines recent developments in improved biosensor technology with mainstream motion-tracking hardware to measure the overall performance of human movement based on joint axis-angle representations of limb rotation. This study proposes an alternative approach to representing three-dimensional rotations using a normalized vector around which an identified joint angle defines the overall rotation, rather than a traditional Euler angle approach. Contrast the procedure of Euler angles with the procedure of Axis angle, Euler angles force the body to move along a certain route which it had arbitrarily chosen but which the body had not chosen; in fact, the body would not take any of its routes separately, though it would take all of them together in the most embarrassing manner-goal-directed behavior. But axis angle had no preconceived scheme as to the nature of the movements to be expressed. Although the axis-angle representation requires vector quotient algebra (quaternions) to define rotation, this approach may be preferred for many graphics, vision, and virtual reality software applications. Elbow flexion and extension motion was used to validate the analytical methods. The results suggest that the novel approach could reasonably predict a detailed analysis of axis-angle migration. The described algorithm could play a notable role in the biomechanical analysis of human joints and offers a harbinger of IMU-based biosensors which may assess the control of skilled manipulation.